The Long Road to Probation Completion: A Longitudinal Analysis of the Effect of Life Events on Re-Arrest among Probationers. Issue 4 (3rd April 2022) - Guo, Siying; Metcalfe, Christi
ABSTRACT: Although much effort has been taken to investigate probation failure and associated factors, less attention has been given to the stability and change in life events during the probation period that could influence probation violations, including re-arrest. Using data from the National Longitudinal Survey of Youth 1997 and survival analyses, the current study aimed to explore the likelihood of probation failure by re-arrest and survival time to re-arrest among those with stable and changing statuses of various social bonds, including marriage/cohabitation and employment. The results suggested that those experiencing stability in these life domains when entering probation initially did not seem to have the best chance of survival. Rather, it was change in these statuses that made a difference. Based on postestimation survival curves, those divorced/separated and unemployed experienced the quickest time to failure.